Mycobacteriosis in Farmed Sea Bream (Sparus aurata) Caused By Mycobacterium frederiksbergense in Turkey - Urku Cigdem (Sciendo, 2018)
Over the past decades, different mycobacteriosis agents have become important fish pathogens. The present study describes a different mycobacteriosis in farmed sea bream (Sparus aurata) caused by Mycobacterium frederiksbergense in Turkey. Affected 15 fish, weighing 15 to 20 g, showed lethargy, stunted growth, pale skin, dorsal fin necrosis, and a significant level of mortality (40 %) in fish stocks. Internally, no multifocal white-colored granulomas in the visceral organs were observed. Inoculation of the visceral organs onto Löwenstein-Jensen medium and Tryptic Soy Agar (1.5% NaCl) slants produced only fast-growing (2-3 weeks), orange to yellow-colored, photochromogenic acid-fast colonies. Ziehl-Nielsen positive bacterial isolates were identified using a commercially available line probe assay (Genotype Mycobacterium CM/AS assay) and with 16S rRNA gene sequencing analysis based on 16S rRNA gene sequencing, fifteen isolates were identified as Mycobacterium frederiksbergense. Histopathologically, epithelioid cell granulomas were not observed in any vicseral organs but acid-fast bacteria were detected in the liver, kidney, spleen, and heart tissue. This study shows that asystemic mycobacteriosis is observed in sea bream with high mortality.